p63 expression defines a lethal subset of muscle-invasive bladder cancers. - Woonyoung Choi (PLoS ONE, 2012)
p63 is a member of the p53 family that has been implicated in maintenance of epithelial stem cell compartments. Previous studies demonstrated that p63 is downregulated in muscle-invasive bladder cancers, but the relationship between p63 expression and survival is not clear.We used real-time PCR to characterize p63 expression and several genes implicated in epithelial-to-mesenchymal transition (EMT) in human bladder cancer cell lines (n = 15) and primary tumors (n = 101). We correlated tumor marker expression with stage, disease-specific (DSS), and overall survival (OS). Expression of E-cadherin and p63 correlated directly with one another and inversely with expression of the mesenchymal markers Zeb-1, Zeb-2, and vimentin. Non-muscle-invasive (Ta and T1) bladder cancers uniformly expressed high levels of E-cadherin and p63 and low levels of the mesenchymal markers. Interestingly, a subset of muscle-invasive (T2-T4) tumors maintained high levels of E-cadherin and p63 expression. As expected, there was a strongly significant correlation between EMT marker expression and muscle invasion (p<0.0001). However, OS was shorter in patients with muscle-invasive tumors that retained p63 (p = 0.007).Our data confirm that molecular markers of EMT are elevated in muscle-invasive bladder cancers, but interestingly, retention of the "epithelial" marker p63 in muscle-invasive tumors is associated with a worse outcome.